Prevalence, Antimicrobial Susceptibility Pattern of Bacterial Isolates, and Associated Factors of Urinary Tract Infections among HIV‐Positive Patients at Hiwot Fana Specialized University Hospital, Eastern Ethiopia - Dadi Marami; Senthilkumar Balakrishnan; Berhanu Seyoum (Canadian Journal of Infectious Diseases and Medical Microbiology)
Urinary tract infection remains a major public health problem in developing countries, where there are limited health-care services. Its prevalence is fueled by human immunodeficiency virus (HIV) infection. The emergence of antimicrobial resistance is now widespread and poses a serious clinical threat. This study investigated the prevalence, antimicrobial susceptibility pattern of bacterial isolates, and associated factors of urinary tract infections among HIV-positive adult patients. A cross-sectional study was conducted among 350 randomly selected HIV-positive patients at Hiwot Fana Specialized University Hospital from February to March 2016. Data were collected using a structured questionnaire. Clean-catch midstream urine samples were collected aseptically and examined using the recommended culture methods. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disk diffusion technique. Data were analyzed using Statistical Package for the Social Sciences version 21.0. The logistic regression models were used to explore the predictors of the outcome. A p value < 0.05 was considered statistically significant. The overall prevalence of urinary tract infection was 18% (95% CI: 15.34–22.63). Individuals with age 35–44 years (Adjusted odds ratio (AOR): 4.07; 95% CI: 1.09, 5.10), income less than 46.7 USD (AOR: 2.76; 95% CI: 1.15, 6.07), and a CD4+ count less than 200 cells/mm3 (AOR: 2.07; 95% CI: 1.15, 3.73) had higher odds of UTI. Escherichia coli (38.1%), Klebsiella pneumoniae (23.8%), and Staphylococcus aureus (11.1%) were the predominant causes of urinary tract infection. E. coli was resistant to ampicillin (95.8%), ceftazidime (95.8%), cotrimoxazole (95.8%), amoxicillin (91.7%), ceftriaxone (87.5%), and tetracycline (87.2%). Multidrug resistance was observed in 46% of the isolates. The prevalence of urinary tract infection in this study was high compared to the previous reports in Ethiopia. Age 35–44 years, income less than 46.7 USD, and a CD4+ count < 200 cells/mm3 increase the odds of urinary tract infection. The most common isolates were E. coli, K. pneumoniae, and S. aureus. Almost half of the isolates were multidrug resistant. Actions to help mitigate the further spread of resistance are urgently needed in the study area.